Pharmacomicrobiomics: a new field contributing to optimizing drug therapy in Parkinson’s disease - Yi Zhang; Chengjun Mo; Penghui Ai; Xiaoqin He; Qin Xiao; Xiaodong Yang (Gut Microbes)
Gut microbiota, which act as a determinant of pharmacokinetics, have long been overlooked. In recent years, a growing body of evidence indicates that the gut microbiota influence drug metabolism and efficacy. Conversely, drugs also exert a substantial influence on the function and composition of the gut microbiota. Pharmacomicrobiomics, an emerging field focusing on the interplay of drugs and gut microbiota, provides a potential foundation for making certain advances in personalized medicine. Understanding the communication between gut microbiota and antiparkinsonian drugs is critical for precise treatment of Parkinson’s disease. Here, we provide a historical overview of the interplay between gut microbiota and antiparkinsonian drugs. Moreover, we discuss potential mechanistic insights into the complex associations between gut microbiota and drug metabolism. In addition, we also draw attention to microbiota-based biomarkers for predicting antiparkinsonian drug efficacy and examine current state-of-the-art knowledge of microbiota-based strategies to optimize drug therapy in Parkinson’s disease.